Two Years Before the Mast - Dana, Richard Henry (Saga Egmont, 2023)
Most people go to an optician if their vision is bad. However, when Richard Henry Dana's sight was affected by measles while he was at Harvard College, he decided a sea voyage round Cape Horn was the best solution. He joined the crew of a merchant ship at Boston, kept a daily diary of his adventures, then produced this American classic. 'Two Years Before the Mast' is a vivid account of the true life of a common sailor at sea. Throughout his journey, Dana encounters indigenous people, describes being lowered down a cliff to retrieve cow hides, learns Spanish, acts as interpreter, and witnesses floggings. The return journey is hellish, and Dana's description of battling storms around the Cape moved 'Moby Dick' author, Herman Melville, to say it "must have been written with an icicle". A rollicking memoir that is better than fiction, ´Two Years Before the Mast´ is perfect for fans of the 'Bounty Trilogy' by Charles Nordhoff and James Norman Hall. Richard Henry Dana Jr. (1815-1882) was a Massachusetts-based American lawyer and politician who found fame for the classic memoir 'Two Years Before the Mast'. In both his legal career and his writing, he gained a reputation for standing up for the rights of the oppressed, including slaves on the run and freedmen. He became a prominent abolitionist, helping to found the anti-slavery Free Soil Party.